Foreign Institutional Investment, Stock Market, and Volatility: Recent Evidence from India - Majumder, Sayantan Bandhu; Nag, Ranjanendra Narayan (Indian Journal of Finance, 2013)
The paper makes an attempt to explore the linkages between the flow of foreign institutional investment (FII), stock market returns and their volatility after the outburst of the global financial crisis in the context of India. The analysis is based on the auto regressive conditional heteroscedasticity (ARCH) family of the model. To the best of our knowledge, this technique has hardly been used in the existing literature on FII flow, stock market returns and their volatility. Analyzing the daily data from January 2008 to February 2012, the present paper finds that higher stock market returns amplify the volume and volatility of the FII flow without any evidence on the other direction. Moreover, the intraday and overnight stock market returns have different implications for FII flow and its volatility. The paper also finds that the flow of FIIs has no significant effect on inducing volatility in the stock market.